2016
DOI: 10.1007/s11096-016-0317-2
|View full text |Cite
|
Sign up to set email alerts
|

Role of clinical pharmacist in the management of blood pressure in dialysis patients

Abstract: Background Hypertension is highly prevalent yet undertreated condition in hemodialysis patients. Objective The objective of this study was to evaluate clinical pharmacist's role in the management of blood pressure in hemodialysis patients guided by home blood pressure monitoring. Setting Outpatient hemodialysis units of Jordan University Hospital and Isra'a Hospital. Method This was a randomized controlled study. It lasted 6 months (September 2011 till the end of March 2012). All hypertensive patients receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 24 publications
4
30
0
Order By: Relevance
“…The proportion of patients whose blood pressure declined after received several counseling sessions were higher compared to that in the control group, significantly in terms of predialysis and intradialysis blood pressure, with some confounders namely sex, age, and education level as in Tables 5 and 6. The result was in line with studies that also showed positive outcome in home blood pressure control involving patient education or collaboration care of pharmacist and physician in the management of blood pressure in dialysis patients 31 .…”
Section: Discussionsupporting
confidence: 86%
“…The proportion of patients whose blood pressure declined after received several counseling sessions were higher compared to that in the control group, significantly in terms of predialysis and intradialysis blood pressure, with some confounders namely sex, age, and education level as in Tables 5 and 6. The result was in line with studies that also showed positive outcome in home blood pressure control involving patient education or collaboration care of pharmacist and physician in the management of blood pressure in dialysis patients 31 .…”
Section: Discussionsupporting
confidence: 86%
“…However, it tended to increase screening of previously unscreened patients (78.6% in the pharmacist MTM group compared to 33.3% in the control group; (OR 7.3, 95% CI: 0.96–56.3; p = 0.05). Qudah et al (2016) Jordan [ 32 ] Randomised controlled study (6 months) Outpatient haemodialysis units of a university hospital To evaluate clinical pharmacists role in the management of blood pressure in haemodialysis patients guided by home blood pressure monitoring 60 HD patients Intervention 55.3 (15.1), and control 51.7 (18.5) Physician-pharmacist collaborative care to optimize antihypertensive pharmacologic therapy (n = 29) Control group (n = 27) 46% of patients in the intervention arm achieved BP target (mean home BP ≤ 135/85 mmHg) compared to only 14.3% of patients in the control arm ( p = 0.02). Average decline in weekly mean home SBP was 10.9 ± 17.7 mmHg in the intervention arm ( p = 0.004) Weekly mean home systolic blood pressure increased by 3.5 ± 18.4 mmHg in the control arm ( p = 0.396) Chia et al (2017) Singapore [ 52 ] Non-randomised, controlled study (24 months) Outpatient nephrology clinic of a tertiary hospital To determine whether a collaborative care (CC) model with pharmacist involvement can reduce admissions and healthcare utilization in patients receiving dialysis, compared to usual care (UC) 134 patients CC 62 (11.4), UC 60.4 (10.8) Pharmacists performed medication review, disease and medication counselling.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of processes (often labelled as interventions) included medication chart review to identify any drug-related problems (DRPs) [ 15 31 ]. Many studies reported pharmacists’ interventions in: modifying drug doses and recommending new pharmacotherapy; [ 16 , 19 , 21 – 23 , 25 – 27 , 29 , 30 , 32 40 , 52 , 59 ]; interacting with a member of the multidisciplinary team; [ 15 17 , 19 21 , 23 – 25 , 27 , 31 , 32 , 34 38 , 40 43 ] requesting and monitoring laboratory parameters; [ 15 , 23 , 25 , 27 , 33 , 34 , 36 , 37 , 43 ] assessing appropriateness of medications prescribed for hospitalised patients at each point of care; [ 17 , 22 , 29 , 30 , 35 38 , 40 , 57 ]. Fewer studies described pharmacist processes at out-patient, pharmacist-led clinics relating to the management of specific CKD complications, such as anaemia; [ 34 , 39 , 44 ] hypertension and diabetes; [ 54 ] managing hypertension through telemedicine; [ 41 ] optimising dyslipidaemia management; [ 37 , 45 ] improving haemoglobin A1c levels (HbA1c); [ 43 ] and emphasising smoking cessation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second is provider-centered care delivery. The focus of this model is on physician support, with the assistance of nurses, clinical pharmacists, medical educators, dietitians, or clinical decision support algorithms [4045]. The third and latest approach is centered on the combination of both models [4651].…”
Section: Discussionmentioning
confidence: 99%